EU ger eko bland korna : från uppbundet till lösdrift - Gustafsson, Ingrid (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2005)
For hundreds of years there has been a tradition with tethered dairy cows in Sweden. The last decades the old fashioned way to hold cows have been questioned and the number of dairy cows in loose housing has been increasing. Last year (2004) 19 percent in total of all farms with milk production in Sweden had their cows in loose housing. Because of EU-legislation concerning all organic production no farms are allowed to build tie stalls any more and after 2010 all organic dairy cows are supposed to live in loose-housing systems. The aim of the thesis was mainly to find out the number of farms with tethered organic dairy cows and if they will continue after the year 2010. Furthermore the purpose was to study if there are any regional differences, how countries similar to Sweden interpret the EU-decision about tethered cows and differences in buildings between organic and conventional farms and the reasons to them. To conclude two suggestions of loose housing for 30 organic dairy cows were made and the building costs were estimated. There are important differences between buildings made for conventional dairy cows and organic ones. Some examples from organic rules are that calf and cow are allowed to go together during the whole colostrums period and the area per animal in some cases is bigger. That often makes organic buildings for dairy cows more expensive to build than conventional ones. In the end of 2004 60 percent of the organically kept dairy cows, which is equivalent to 40 percent of the farms in Sweden, were already in loose-housing systems depending on that decision. There are big regional differences. The information that these results are based on was collected from the controllers of KRAV and the farmers themselves. The legislation is known amongst the affected milk producers, but the uncertainty if they will continue their production or not is widely spread. 48 percent are estimated to continue, 10 percent to quit and 42 percent are uncertain whether they will continue to produce organic milk or not after the year 2010. The estimations were made out of the assessments of approximately half of the KRAV controllers. After interviewing a number of farmers who have tied-up cows and soon probably will have to build a loose-housing system I became aware of how they hope to handle the changeover. The conclusion made was that they hope to be able to get a bankloan, find second-hand equipment and use building materials of their own and do as much of the work as possible themselves. Different countries within EU have construed the legislation about dairy cow housing in different ways and in Denmark for example all tethered cows have to be taken out daily. The other Scandinavian countries are waiting for the EU-commission's report on the implementation of the provision about what size "small holdings" are. I have got the information about the different interpretations by reading the legislation of the countries and from personal contact with people working on these questions. Depending on how the subsidy for new investments in the agriculture is designed and how the agricultural politics in general is working it affects the amount of loose-housing systems and the 6 size of the stocks in different parts of Sweden. I got the impression, during my field trip in February 2005, that the situation is similar in Denmark and Norway. Two suggestions, including drawings, for loose-housing systems for 30 cows have been made and the building cost was estimated at approximately 3 to 3,4 million Swedish crowns. This thesis is written at the request of the Swedish Dairy Association (Svensk Mjölk).